From Indonesia to China: The Evolving Landscape of Santri Diplomacy - Xue Song; Virdika Rizky Utama (ISLAM NUSANTARA:Journal for the Study of Islamic History and Culture, 2025)
This paper critically examines existing research on santri diplomacy, focusing on its development, challenges, and unique characteristics in China. While Nahdlatul Ulama (NU) and Muhammadiyah lead santri diplomacy efforts globally, in China, individual santri figures have gained influence through social media. Due to China’ s regulations on religious activities, santri diplomacy in China primarily functions as cultural rather than faith-based diplomacy, focusing on enhancing Indonesia’s image and fostering mutual understanding. Furthermore, santri often engage in reverse advocacy, clarifying misconceptions about China’s religious landscape to Indonesian Muslims. As China-Indonesia ties deepen, the importance of santri diplomacy will grow, necessitating the empowerment of Islamic organizations and figures in China to foster more effective people-to-people exchanges.